Pengembangan Multimedia Pembelajaran Interaktif Untuk Mata Kuliah Organisasi Komputer - Bambang Eka Purnama; Wawan Saputra - Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT - In the era of Information Technology, the use of computers has penetrated into all areas of life, including in the world of education. Computers have practical application programs that can be utilized and developed for the achievement of educational goals. Some of the orientations of using computers in education are how computers can help people to learn, to teach, and to help people manage education in general. Likewise in the development of learning materials or materials, as an alternative learning resource, computers are used to transfer materials to students or in this context commonly referred to as computer-based learning materials.In a more innovative and interactive learning system, teachers will always be required to be creative and innovative in finding learning breakthroughs capable of combining text, images, audio, music, animated images or videos in a mutually supportive unit in order to achieve learning objectives capable of causing a sense of pleasure during the learning process. teaching and learning process takes place. This will increase student motivation during the teaching and learning process to obtain maximum learning objectives.It can be concluded that this Interactive Learning Media can help users in independent learning. In addition, the attractive appearance and existing sound facilities make the user more interested in learning. The application program that the author created can be used for learning Computer Organization course material. BackgroundIn the era of Information Technology, the use of computers has penetrated into all areas of life, including in the world of education. Computers have practical application programs that can be utilized and developed for the achievement of educational goals. Some of the orientations of using computers in education are how computers can help people to learn, to teach, and to help people manage education in general. Likewise in the development of learning materials or materials, as an alternative learning resource, computers are used to transfer materials to students or in this context commonly referred to as computer-based learning materials. One of them is learning the Computer Organization course. Sometimes students have difficulty understanding material that introduces many types of hardware and their grouping. So it is necessary to find a learning method that attracts students to be more diligent in studying it, including by utilizing computer technology. Based on this, the use of computer technology in the field of learning in the form of interactive CDs was developed on the basis of the assumption that the communication process in learning will be more attractive to students and provide convenience for understanding the material because of its interactive presentation, by utilizing various media as a means of supporting learning activities. Interactive media can be interpreted as a combination of various media elements consisting of text, graphics, photos, animations, videos, and sounds that are presented interactively in learning media.Keywords – multimedia, learning, interactive, computer organization ABSTRAKSI - Dalam era Teknologi Informasi penggunaan komputer telah merambah ke segala bidang kehidupan, termasuk dalam dunia pendidikan. Komputer memiliki program-program aplikasi praktis yang dapat dimanfaatkan dan dikembangkan untuk pencapaian tujuan pendidikan. Beberapa orientasi penggunaan komputer dalam dunia pendidikan adalah bagaimana komputer dapat membantu orang untuk belajar, untuk mengajar, dan membantu orang dalam mengelola pendidikan secara umum. Begitu juga dalam pengembangan bahan-bahan atau materi pembelajaran, sebagai alternatif sumber belajar, komputer digunakan untuk mentransfer materi-materi kepada peserta didik atau dalam konteks ini biasa disebut dengan bahan pembelajaran berbasis komputer.Pada Sistem pembelajaran yang lebih inovatif dan interaktif, pengajar akan selalu dituntut untuk kreatif inovatif dalam mencari terobosan pembelajaran mampu mengabungkan antara text, gambar, audio, musik, animasi gambar atau video dalam satu kesatuan yang saling mendukung guna tercapainya tujuan pembelajaran mampu menimbulkan rasa senang selama proses belajar mengajar berlangsung. Hal ini akan menambah motivasi mahasiswa selama proses belajar mengajar hingga didapatkan tujuan pembelajaran yang maksimal.Dapat disimpulkan bahwa Media Pembelajaran Interaktif ini dapat membantu user dalam pembelajaran yang mandiri. Selain itu, tampilan yang menarik dan fasilitas suara yang ada membuat user lebih tertarik untuk belajar. Program aplikasi yang penulis buat ini dapat dipergunakan untuk pembelajaran materi matakuliah Organisasi Komputer. Latar BelakangDalam era Teknologi Informasi penggunaan komputer telah merambah ke segala bidang kehidupan, termasuk dalam dunia pendidikan. Komputer memiliki program-program aplikasi praktis yang dapat dimanfaatkan dan dikembangkan untuk pencapaian tujuan pendidikan. Beberapa orientasi penggunaan komputer dalam dunia pendidikan adalah bagaimana komputer dapat membantu orang untuk belajar, untuk mengajar, dan membantu orang dalam mengelola pendidikan secara umum. Begitu juga dalam pengembangan bahan-bahan atau materi pembelajaran, sebagai alternatif sumber belajar, komputer digunakan untuk mentransfer materi-materi kepada peserta didik atau dalam konteks ini biasa disebut dengan bahan pembelajaran berbasis komputer. Salah satunya adalah pembelajaran mata kuliah Organisasi Komputer. Terkadang mahasiswa kesulitan dalam memahami materi yang memperkenalkan banyaknya jenis-jenis hardware serta pengelompokkannya. Maka perlu dicari metode pembelajaran yang menarik minat mahasiswa untuk lebih tekun mempelajarinya, di antaranya dengan memanfaatkan teknologi komputer. Berdasarkan hal tersebut, pemanfaatan teknologi komputer di bidang pembelajaran berupa CD interaktif dikembangkan atas dasar asumsi bahwa proses komunikasi di dalam pembelajaran akan lebih menarik minat mahasiswa dan memberikan kemudahan untuk memahami materi karena penyajiannya yang interaktif, dengan memanfaatkan berbagai media sebagai sarana penunjang kegiatan pembelajaran. Media interaktif dapat di artikan sebagai kombinasi berbagai unsur media yang terdiri dari teks, grafis, foto, animasi, video, dan suara yang disajikan secara interaktif dalam media pembelajaran.Kata Kunci – multimedia, pembelajaran, interaktif, organisasi komputer